PENGUATAN MODAL SOSIAL DALAM RANGKA PEMBERDAYAAN ANGGOTA KLASTER MAKANAN RINGAN DI KOTA MAGELANG - Soebandriyo Soebandriyo (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2012)
Research Goal: 1) To know the problems society strengthening social capital cluster members in order to develop food [light / mild] cluster Magelang, 2) For the rectification Strengthening social capital cluster members in order to develop food [light / mild] cluster Magelang, 3) formulate and develop reinforcement model image of the community members of social capital clusters [lit / illuminated] Magelang food city. Type a descriptive qualitative research, informant [cover / lid]: Cluster members [lit / illuminated] food, Magelang BAPPEDA officer, Officer Disperindag Magelang, Officer FEDEP Magelang, and one of the colleges there Magelang Research classify cluster members [lit / illuminated] food less active activity classify, if invited to attend group meetings several activities so that lack of information, and do not get / the trust of the other members of the group. [Way / Method] alignment existence [of; know about] the collective participation of members of the cluster [lit / illuminated] study the issues of food and also take action with. Model Development-An Image of social capital (in) allows members of the cluster [lit / illuminated] Magelang food city, [which] are as follows: model of investment as at (in) the egalitarian social structure (familiarity), and the model allows agents reformer